Optical and scintillating properties of Cs-doped (PEA)2PbBr4 perovskite crystals - Maddalena, Francesco (2025)
Inorganic ion doping has emerged as a promising approach to enhance the scintillation properties of two-dimensional (2D) organic-inorganic hybrid perovskite (OIHP) crystals, particularly by increasing mass density and effective atomic number (Z). In this study, we investigate the effects of cesium (Cs) doping on (PEA)2PbBr4. Our findings indicate that Cs-doping in (PEA)2PbBr4, especially above 5 %, results in the formation of local quasi-2D domains within the grown crystal and even bulk domains at higher concentrations. This leads to an overall narrowed band gap, reduced by as much as 0.2 eV compared to the undoped material. Cs-doping also broadens photoluminescence (PL) spectra and significantly accelerates PL decay times, achieving fast as (1.1 ± 0.1) ns, with an average decay time reduction of 81 % compared to undoped crystals. Furthermore, the inclusion of Cs ions shortens scintillation decay times, reaching as fast as (51.6 ± 5.7) ns, with an average decrease of 10 %. Notably, Cs-doping at a threshold concentration of 5 % leads to a 30 % improvement in light yields (LYs). These results demonstrate that Cs-doping significantly enhances the performance of (PEA)2PbBr4 crystals, making them particularly well-suited for high LYs and fast timing applications, such as photon counting and positron emission tomography. This study underscores the potential of Cs-doped OIHP crystals in advancing the capabilities of scintillation-based radiation detection technologies.